Determination of Marketing Strategy in SMEs UD. Albarokah Based on 4P Strategy, Promotion Mix, Public Relations - Maulana Maghfur; Said Salim Dahda (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
UD. Albarokah is a trading business one of which produces snack that we often eat daily namely mini opaque with three flavors, namely original, spicy, and green beans. In the study, the Analytical Hierarchy Process (AHP) method is used to get right priority of marketing strategy proposals, which can be applied to compaines to increase sales volume. The results of the priority alternative marketing strategies from the highest to the lowest are product strategy being the first priority choice, promotion strategy being the second choice, price strategy being the third choice, place strategy being the fourth choice, public relations strategy being the fifth choice. The recommendations for alternative strategies given are product packaging, trustworthy information messages, easily accessible information discovery, affordable prices, clear and easy-to-understand information, product quality, attractive prices discounts, ease of payment selection. UD. Albarokah adalah bisnis perdagangan yang salah satunya memproduksi makanan ringan yang sering kita makan sehari-hari yaitu opak mini dengan tiga rasa yakni original, pedas, dan kacang ijo. Pada penelitian ini, metode Analytical Hierarchy Process (AHP) digunakan untuk mendapatkan prioritas usulan strategi pemasaran yang tepat, yang dapat diterapkan pada perusahaan untuk meningkatkan volume penjualan. Hasil prioritas strategi pemasaran dari yang tertinggi sampai yang terendah yaitu strategi produk menjadi pilihan prioritas pertama, strategi promosi menjadi pilihan kedua, strategi harga menjadi pilihan ketiga, strategi tempat menjadi pilihan keempat, strategi hubungan masyarakat menjadi pilihan kelima. Rekomendasi alternatif strategi yang diberikan yaitu kemasan produk, pesan informasi dapat dipercaya, penemuan informasi mudah diakses, harga yang ditawarkan terjangkau, informasi bersifat jelas dan mudah dipahami, kualitas produk, potongan harga yang ditawarkan menarik, kemudahan pemilihan pembayaran.